2021
DOI: 10.1101/2021.01.20.21250141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serum proteome analysis of systemic JIA and related pulmonary alveolar proteinosis identifies distinct inflammatory programs and biomarkers

Abstract: ObjectivesRecent observations in systemic Juvenile Idiopathic Arthritis (sJIA) suggest an increasing incidence of high-mortality interstitial lung disease (ILD), characterized pathologically by a variant of pulmonary alveolar proteinosis (PAP). The co-occurrence of macrophage activation syndrome (MAS) and PAP in sJIA suggested a shared pathology, but features of drug reaction such as anaphylaxis, rashes, and eosinophilia are also common in these patients. We sought to investigate immunopathology and identify b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
(117 reference statements)
1
10
0
Order By: Relevance
“…In recent sJIA serum proteomics studies using SOMAscan, a total of 1317 protein sets were used for the analysis. 12 In comparison to the total proteins obtained in our analysis, 570 proteins overlapped, but many unique proteins were also obtained in each of the analyses ( Figure S2A ). Focusing on the proteins that changed during the active phase of sJIA, 55 proteins were found in common, despite differences in the comorbidities and race of the patients studied ( Figure S2B and Table S3 ).…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…In recent sJIA serum proteomics studies using SOMAscan, a total of 1317 protein sets were used for the analysis. 12 In comparison to the total proteins obtained in our analysis, 570 proteins overlapped, but many unique proteins were also obtained in each of the analyses ( Figure S2A ). Focusing on the proteins that changed during the active phase of sJIA, 55 proteins were found in common, despite differences in the comorbidities and race of the patients studied ( Figure S2B and Table S3 ).…”
Section: Resultsmentioning
confidence: 74%
“…Recently, it was reported that the analysis of sJIA patient serum using SOMAscan identified a new candidate biomarker and variable protein groups in sJIA that were associated with pulmonary alveolar proteinosis (PAP). 12 Thus, detailed studies of changes in serum protein levels using proteome analysis techniques may reveal important factors related to the disease and proteins that can serve as new biomarkers, which may provide clues to understanding the pathogenesis of the disease. In this study, we performed a proteomic analysis of sJIA serum by overlapping window DIA-MS to evaluate the performance of the analytical approach and reveal changes in proteome profiling according to disease activity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using serum proteome analyses of 162 patients, Chen et al recently underlined the importance of IL-18 as it was stronger upregulated in sJIA patients with LD as compared to those without. Also, they identified ICAM5, a cell adhesion molecule, as a potential biomarker that is specifically upregulated in sJIA-LD (and not in general sJIA or MAS) and might be able to detect patients at risk at an early timepoint (43). However, this finding has not been replicated for AOSD-LD so far.…”
Section: Diagnosticsmentioning
confidence: 98%